Comparative analysis of the results of the introduction of a structural and functional model of the development of legal competence of medical specialists in postgraduate education - Kharkivsky, V. S. (Problems of Engineer-Pedagogical Education, 2018)
The article presents a comparative analysis of the results of the pilot phase of the pedagogical experiment, during which there was an experimental introduction of the structural and functional model of the development of legal competence (LC) of medical specialists in postgraduate education (PO). It was noted that the introduction of the structural-functional model of the system of the development of legal competence of specialists in the medical sector in postgraduate education took place during the formative stage of the pedagogical experiment and followed such steps as preliminary, auxiliary and principal. The qualimetric model of the assessment of the development of legal competence of medical specialists in postgraduate education is presented. The research results have confirmed the hypothesis that the development of LC of specialists in the medical field in PO will be more effective if it is based on a reasonable theoretical foundation (a methodological integrated approach that involves the synthesis of competence, activity, personality-oriented, acmeological and systemic approaches; the paper also defines principles and functions of the development of this competence).